Taxonomic revision of the Malagasy Aphaenogaster swammerdami group (Hymenoptera: Formicidae) - Csősz, Sandor; Loss, Ana C.; Fisher, Brian L. (PeerJ, 2021)
Background Madagascar is famous for its extremely rich biodiversity; the island harbors predominantly endemic and threatened communities meriting special attention from biodiversity scientists. Continuing ongoing efforts to inventory the Malagasy ant fauna, we revise the species currently placed in the myrmicine genus Aphaenogaster Mayr. One species described from Madagascar, Aphaenogaster friederichsi Forel, is synonymized with the Palearctic A. subterranea Latreille syn. nov. This species is considered neither native to Madagascar nor established in the region. This revision focuses on the balance of species in the A. swammerdami group which are all endemic to Madagascar. Methods The diversity of the Malagasy Aphaenogaster fauna was assessed via application of multiple lines of evidence involving quantitative morphometric, qualitative morphological, and DNA sequence data. (1) Morphometric investigation was based on hypothesis-free Nest Centroid clustering (NC-clustering) combined with PArtitioning based on Recursive Thresholding (PART) to estimate the number of morphological clusters and determine the most probable boundaries between them. This protocol provides a repeatable and testable approach to find patterns in continuous morphometric data. Species boundaries and the reliability of morphological clusters recognized by these exploratory analyses were tested via confirmatory Linear Discriminant Analysis (LDA). (2) Qualitative, external morphological characteristics (e.g., shape, coloration patterns, setae number) were subjectively evaluated in order to create a priori grouping hypotheses, and confirm and improve species delimitation. (3) Species delimitation analyses based on mitochondrial DNA sequences from cytochrome oxidase I (COI) gene fragments were carried out to test the putative species previously delimited by morphological and morphometric analyses. Results Five species can be inferred based on the integrated evaluation of multiple lines of evidence; of these, three are new to science: Aphaenogaster bressleri sp. n., A. gonacantha (Emery, 1899), A. makay sp. n., A. sahafina sp. n., and A. swammerdami Forel, 1886. In addition, three new synonymies were found for A. swammerdami Forel, 1886 (A. swammerdami clara Santschi, 1915 syn. n., A. swammerdami curta Forel, 1891 syn. n. and A. swammerdami spinipes Santschi, 1911 syn. n.). Descriptions and redefinitions for each taxon and an identification key for their worker castes using qualitative traits and morphometric data are given. Geographic maps depicting species distributions and biological information regarding nesting habits for the species are also provided.
Keywords: Biodiversity; Entomology; Taxonomy; Morphometry; Biogeography; New species; Phylogeny